Design of multi-target hybrid molecules for synergistic therapy of malaria and human African trypanosomiasis - Barack Ndenga (Publisher, 2025)
The increasing resistance of Plasmodium spp. and Trypanosoma brucei to conventional antimalarial and trypanocidal drugs poses a major challenge for global health. In response, this study introduces a computationally-driven hybrid multi-target drug design strategy, using AutoEvoChem V2.0, a platform developed by the author. I propose a series of unprecedented candidate molecules derived from drug repurposing and rational hybrid design, including derivatives of Rufinamide, Disulfiram, Clofazimine, Sulforaphane, and Benserazide. These hybrids combine molecular fusion, controlled pro-oxidant motifs, peptide targeting, and nanoparticle encapsulation, aiming to enhance efficacy and selectivity against malaria and human African trypanosomiasis (HAT). Computational docking and ADMET predictions indicate that these hybrids possess strong multi-target activity, synergistic mechanisms, and favorable pharmacokinetic properties, potentially overcoming limitations of current monotherapies. This study establishes a proof-of-concept framework for designing next-generation multi-mode anti-parasitic therapies and highlights the potential of computational innovation in accelerating drug discovery for neglected diseases.
Cet ensemble de données et l'article de recherche qui l'accompagne présentent une nouvelle approche pour la conception rationnelle de molécules hybrides ciblant à la fois le paludisme (Plasmodium spp.) et la trypanosomiase humaine africaine (Trypanosoma brucei). Grâce à la plateforme informatique AutoEvoChem V2.0, une série de molécules hybrides inédites a été conçue par réorientation de médicaments, modification chimique et optimisation multicible. L'étude met en évidence l'intégration de dérivés halogénés, de motifs pro-oxydants, de ciblage peptidique et d'encapsulation de nanoparticules pour renforcer les effets synergétiques contre les parasites. L'ensemble de données comprend : Structures moléculaires 2D et 3D de cinq molécules hybrides (iodure de rufinamide + chloroquine, disulfirame + méfloquine bromée, clofazimine + luméfantrine iodée, sulforaphane modifié + amodiaquine, iodure de bensérazide + artéméther) Tableaux résumant les modifications moléculaires, les propriétés ADMET prévues et les effets synergiques attendus Un aperçu schématique des mécanismes multi-cibles démontrant la rupture de la membrane, l'inhibition enzymatique, le blocage métabolique et l'induction du stress oxydatif Cet ouvrage offre des ressources précieuses aux chercheurs en chimie médicinale, en parasitologie et en découverte de médicaments axés sur les maladies tropicales négligées.